2015
DOI: 10.1155/2015/846807
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Atorvastatin on Arterial Stiffness in Male Patients with Type 2 Diabetes

Abstract: Statin therapy improves lipid profiles and reduces vascular inflammation, but its effects on central arterial stiffness in type 2 diabetes are unclear. The aim of this study was to determine whether statin therapy reduces central arterial stiffness, in a dose-dependent manner, in male patients with type 2 diabetes. Fifty-one patients ceased statin therapy for 6 weeks, followed by randomisation to either 10 or 80 mg of atorvastatin. At randomization, 3 and 12 months, central arterial stiffness was measured via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
0
21
2
2
Order By: Relevance
“…In DM patients, insulin was found to regulate the OPG production and vascular calcification in human aortic smooth muscle cells [29], and 24-week treatment of pioglitazone, which was a agonist of peroxisome proliferator-activated receptor gamma, could down-regulate serum levels of OPG as well as CRP [30]. In addition, treating patients with DM or CAD with atorvastatin or simvastatin appeared to lower serum OPG and high-sensitivity CRP as well as reduce arterial stiffness, which indicated beneficial effects of statin on vasculature through anti-inflammation [31,32]. Although studies had shown medications could have modulatory effects on vessels, there were no significant differences of medications between the normal or low ABI groups in this study.…”
Section: Discussionmentioning
confidence: 96%
“…In DM patients, insulin was found to regulate the OPG production and vascular calcification in human aortic smooth muscle cells [29], and 24-week treatment of pioglitazone, which was a agonist of peroxisome proliferator-activated receptor gamma, could down-regulate serum levels of OPG as well as CRP [30]. In addition, treating patients with DM or CAD with atorvastatin or simvastatin appeared to lower serum OPG and high-sensitivity CRP as well as reduce arterial stiffness, which indicated beneficial effects of statin on vasculature through anti-inflammation [31,32]. Although studies had shown medications could have modulatory effects on vessels, there were no significant differences of medications between the normal or low ABI groups in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have identified positive results using antihypertensives 67,68 and hypolipidemic agents. 69,70 The effect of antihypertensives, however, is due to the reduction of blood pressure. Thus, pharmacological treatment for other diseases, associated with the measures mentioned above, which may attenuate the loss of elastic fibers in the arteries, may have an additional effect on the control of arterial stiffness.…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, some authors report that atorvastatin reduces arterial stiffness [51,52], which may occur for its anti-inflammatory actions as COX-2 and oxidative stress reduction, thus contributing to reducing vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%